Evaluation of lambs propensity towards different accessions of Psoralea - Decandia M.; Acciaro M.; Sitzia M.; Cabiddu A.; Manca C.; Molle G.; Giovanetti V. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Animal propensity towards a food is mainly based on pre-ingestive stimuli, and could be measured by the intake rate. A short-term test, using the micro-swards method, was carried out to measure lambs propensity for different accessions of Psoralea genus, a perennial legume widely distributed in Mediterranean regions. The following 4 accessions of Psoralea were evaluated: Psoralea bituminosa crassiuscula Vilaflor; Psoralea bituminosa bituminosa Llano del Beal; Psoralea bituminosa bituminosa Monte Rosello; Psoralea morisiana Punta Giglio. The forages were offered, in a 4x4 latin-square design with 3 replicates, to 12 Sarda lambs, first adapted to the test routine with Hordeum vulgaris L.. Fresh matter intake (FMI) and DM intake (DMI, g head-1), number of bites (NB, n.), eating time (ET, min), bite frequency (BF, n. min-1) and intake rate (IR, g min-1) were measured in 5 min sessions. Overall, lambs showed a low propensity for all accessions of Psoralea with a slightly higher DM IR for Vilaflor (P≤0.05).
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)